Wali dan Karamah dalam Perspektif Tafsir Ishārī Sahl al-Tustarī - Ghozi (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2021)
Abstract: This article analyzes the esoteric interpretation of Sahl al-Tustarī in his work Tafsīr al-Qur’ān al-‘Aẓīm. As a Sufi master well-known for his asceticism, al-Tustarī laid the groundwork of a new phase in disclosing a new formation of the Qur’anic exegesis. His esoteric interpretation does not only provide the inner dimension of the verse, but also shed light on the outer dimensions. Although his work is not completed in interpreting all verses of the Qur’an, it is inevitable that his work has galvanized some later Sufis into writing their exegetical works. Using a descriptive-analytical method, this article scrutinizes the two key concepts of sufism, the sainthood and the charismata, in al-Tustarī’s exegetical work. Both issues are crucial to unravel inasmuch as they are closely enough related to the avowal of sainthood and its acceptability that are still disputable in many Muslims. This article draws conclusions that the sainthood and the charismata in al-Tustarī’s exegetical work are elucidated in the frame of morality and shariah. Al-Tustarī asserts that all saints have their own stages and each stage has its own role and duty both spiritually and socially. Furthermore, al-Tustarī does not consider the charismata (khāriq al-‘ādah) to be something special. In his standpoint, virtue is precisely the most essential part of the charismata.